Fatérfogat meghatározási módszerek megbízhatóságának vizsgálata nyírségi nemes nyár állományokban - Horváth Gábor (2018)
In my thesis I estimated the volume of Pannonia hybrid poplars with several methods int he Nyírség area. I compared my results to both the original and updated values in the forest management plans. I also invesigated the reliability of graphical yield tables (nomograms). The results show that in lot of the cases there are considerable differences between the values which are mainly due to inaccurate height estimation. The thesis also deaés with differences in volume ont he area of the forest estate.